Penetrating Trauma in Children, Our Experience (Medical Forum Monthly, 2020)
Objective: To study the characteristics of patients, management, and outcomes of penetrating thoracic and abdominal trauma in children.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Paediatric Surgery Department Bahawal Victoria Hospital Bahawalpur, from April 2016 to April 2020.Materials and Methods: A total of 93 patients with penetrating to abdomen and thorax were admitted in pediatric surgery department from April 2016 to April 2020. These patients were evaluated with reference to patient’s biodata, their clinical presentation, mode of trauma, management and their outcome.Results: Out of 93 patients admitted to pediatric surgery department with penetrating thoraco abdominal trauma 37 were due to fall from height especially from trees, 27 due to road traffic accidents, 13 because of stabbing and 16 due to firearm injuries. The mean age was 9.73 ± 4.31 [1–16] years. sixty-four were wounded in abdomen ,19 in thorax and10 in both the abdomen and thorax. Fifty-six patients underwent some sort of surgical intervention and remaining 37 patients were conservatively managed. The hospital stay on a mean was 2.47± 3.13 days for pts managed conservatively and 7.37±11.43 days for pts with surgical intervention.Conclusion: The penetrating trauma to abdomen and thorax significantly differ in incidence being more in abdomen. surgical management is the main management option though; conservative may be the other option but with vigilant monitoring. Along with development of management strategies, emphasis on prevention of trauma must be considered.